The Effect of Service Quality, School Image, and Student Satisfaction on Loyalty - Rani, Lala Aulia Sanria; Nugraha, Jaka (Department of Economics Education, Faculty of Economics, Universitas Negeri Semarang, 2021)
This study aimed to determine service quality, school image, and student satisfaction with student loyalty at SMKN 2 Buduran. This study used quantitative research methods. Data were obtained from 50 students at SMKN 2 Buduran Sidoarjo. Analysis of the data used using Google Form as a research medium for service quality, school image, and student satisfaction with student loyalty. The results obtained from the study can be concluded: the quality of school services to students was almost fulfilled. The better the quality of service provided by the school to students, the higher the student loyalty. The image of the school according to students' views was good. The higher the image quality of the school, the higher the loyalty that students had so that students became satisfied while learning. Student satisfaction according to the assessment of students was quite fulfilled. So that the higher the student satisfaction, the higher the student's loyalty to the school. Students' views on service quality, school image, and student satisfaction were almost fulfilled because the higher the loyalty given to students, the higher the students' loyalty to the school so that students felt satisfied in carrying out learning activities at school.